Antepartum and intrapartum stillbirth rates across gestation: a cross-sectional study using the revised foetal death reporting system in the U.S. - Collette N. Ncube; Sarah M. McCormick; Sylvia E. Badon; Taylor Riley; Vivienne L. Souter (BMC, 2022)
Abstract Background There is a renewed call to address preventable foetal deaths in high-income countries, especially where progress has been slow. The Centers for Disease Control and Prevention released publicly, for the first time, the initiating cause and estimated timing of foetal deaths in 2014. The objective of this study is to describe risk and characteristics of antepartum versus intrapartum stillbirths in the U.S., and frequency of pathological examination to determine cause. Methods We conducted a cross-sectional study of singleton births (24-43 weeks) using 2014 U.S. Fetal Death and Natality data available from the National Center for Health Statistics. The primary outcome was timing of death (antepartum (n = 6200), intrapartum (n = 453), and unknown (n = 5403)). Risk factors of interest included maternal sociodemographic, behavioural, medical and obstetric factors, along with foetal sex. We estimated gestational week-specific stillbirth hazard, risk factors for intrapartum versus antepartum stillbirth using multivariable log-binomial regression models, conditional probabilities of intrapartum and antepartum stillbirth at each gestational week, and frequency of pathological examination by timing of death. Results The gestational age-specific stillbirth hazard was approximately 2 per 10,000 foetus-weeks among preterm gestations and > 3 per 10,000 foetus-weeks among term gestations. Both antepartum and intrapartum stillbirth risk increased in late-term and post-term gestations. The risk of intrapartum versus antepartum stillbirth was higher among those without a prior live birth, relative to those with at least one prior live birth (RR 1.32; 95% CI 1.08-1.61) and those with gestational hypertension, relative to those with no report of gestational hypertension (RR 1.47; 95% CI 1.09-1.96), and lower among Black, relative to white, individuals (RR 0.70; 95% CI 0.55-0.89). Pathological examination was not performed/planned in 25% of known antepartum stillbirths and 29% of known intrapartum stillbirths. Conclusion These findings suggest greater stillbirth risk in the late-term and post-term periods. Primiparous mothers had greater risk of intrapartum than antepartum still birth, suggesting the need for intrapartum interventions for primiparous mothers in this phase of pregnancy to prevent some intrapartum foetal deaths. Efforts are needed to improve understanding, prevention and investigation of foetal deaths as well as improve stillbirth data quality and completeness in the United States.